Ring Beam Modulation-Assisted Laser Welding on Dissimilar Materials for Automotive Battery - Se-Hoon Choi; Jong-Hyun Kim; Hae-Woon Choi (Journal of Manufacturing and Materials Processing)
This paper investigates Ring Beam Modulation-assisted Laser (RBML) welding as a novel approach for joining dissimilar materials, specifically aluminum and copper, which are essential in high-performance applications such as electric vehicle batteries and aerospace components. The study aims to address challenges such as thermal mismatches, brittle intermetallic compounds, and structural defects that hinder traditional welding methods. The research combines experimental and computational analyses to evaluate the impact of heat input distributions and laser modulation parameters on weld quality and strength. Three welding cases are compared: fixed center beam with variable ring beam outputs, variable center beam with fixed ring outputs, and a wobble-mode beam to enhance interfacial bonding. Computational modeling supports the optimization process by simulating heat flows and material responses, exploring various shape factors, and guiding parameter selection. Key findings include a nonlinear relationship between heat input and welding strength across the cases. Case 1 demonstrates improved weld strength with higher ring beam input, while Case 2 achieves excellent reliability with relatively lower inputs. Case 3 introduces wobble welding, yielding superior resolution and consistent weld quality. These results confirm that precise ring beam modulation enhances weld reliability, minimizes thermal distortions, and optimizes energy consumption. The manuscript advances the state of knowledge in laser welding technology by demonstrating a scalable, energy-efficient method for joining dissimilar materials. This contribution supports the fabrication of lightweight, high-reliability assemblies, paving the way for innovative applications in the automotive, medical, aerospace, and shipbuilding industries.